Test-enhanced learning: analysis of an experience with undergraduate nursing students. Issue 1 (December 2015) - Messineo, Linda; Gentile, Manuel; Allegra, Mario
Abstract Background This study is based on the evidence that tests can be used as an educational tool to enhance learning, not just as an evaluation tool. There is a growing body of research that shows that participating in repeated testing improves learning, a phenomenon defined as Test-Enhanced Learning. The aim of the present study was to analyse the effect of the use of a test enhanced learning program integrated into a general psychology course for undergraduate nursing students and its interaction with the students' test anxiety. Methods 161 undergraduate nursing students attending a General Psychology course followed an educational program based on Test-Enhanced Learning methodology. Students were divided into two groups, an experimental group (TEL group) and a control group (Re-study group). TEL students took a multiple-choice test on the lecture topics. The Re-study group just read study material. Testing and re-study occurred at intervals of about a week after each lesson. TEL students received feedback immediately after each test. About two weeks after the end of the lessons, all the students took a final cumulative test on all the topics. Statistical analysis was used to analyse students' performances. After the administration of the cumulative unit test, all the students took a graded examination. Results Students in the TEL group performed better than the controls, both in the final cumulative test and in a graded examination. TEL participants experienced better final cumulative test results than students not tested (M TEL = 23.11, M Re-study = 20.47, t (109.86) = −2.57, p < 0.05, r = 0.24). Test-Enhanced Learning program participation has a positive impact on exam performance (βG_Step1 = 0.46, p < 0.001). Finally, the analysis performed shows a slight moderating effect of test anxiety on Test-Enhanced Learning (βGxTA_Step3 = 0.15, p < 0.05). Discussion and Conclusions Test-Enhanced Learning can be an effective tool for promoting and enhancing learning. In fact, taking tests after studying produced better long-term retention and then better final test performance than re-reading without testing. Both students in the TEL group and the Re-study group with a high test anxiety level perform less well than colleagues with lower test anxiety. Nevertheless, students with higher test anxiety may obtain more benefits from participating in a Test-Enhanced Learning process than people with lower test anxiety. Further studies on larger and more representative samples are necessary in order to investigate the effect of test anxiety on Test-Enhanced Learning.